Vaccine hesitancy of the COVID‐19 by health care personnel. Issue 5 (19th December 2020) - Kose, Sukran; Mandiracioglu, Aliye; Sahin, Seheray; Kaynar, Teoman; Karbus, Omer; Ozbel, Yusuf
Abstract: Background: The determination of the acceptance of the COVID‐19 vaccine by the health personnel will also be a guide for the upcoming vaccination studies. The aim of this study is to determine the acceptance status of COVID‐19 vaccine amongst healthcare professionals. Materials and methods: A total of 1138 healthcare workers participated in this cross‐sectional study between 17th and 20th of September, 2020. The questionnaire, which was delivered via social media, was filled out by the participants over "Google Forms." Results: As a result of the questionnaire, 68.6% of the healthcare professionals stated that they could be vaccinated. Men, students, the younger age group, and those who had a previous flu shot were all willing to get the COVID‐19 vaccine. Conclusions: Efforts to increase the knowledge of healthcare professionals about the new vaccine and to eliminate their doubts and concerns are important.